NKG2D and DNAM-1 activating receptors and their ligands in NK-T cell interactions: role in the NK cell-mediated negative regulation of T cell responses - Zingoni, Alessandra; Ardolino, Michele; Santoni, Angela; Cerboni, Cristina (Frontiers in Immunology, 2013)
The negative regulation of adaptive immunity is relevant to maintain lymphocyte homeostasis. Several studies on NK cells have shown a previously unappreciated immunomodulatory role, as they can negatively regulate T cell-mediated immune responses by direct killing and by secretion of inhibitory cytokines. The molecular mechanisms of T cell suppression by NK cells, however, remained elusive. Only in the last few years it has become evident that, upon activation, human T cells express MICA-B, ULBP1-3, and PVR, ligands of the activating receptors NKG2D and DNAM-1, respectively. Their expression renders T cells targets of NK cell lysis, representing a new mechanism taking part to the negative regulation of T cell responses. Studies on the expression of NKG2D and DNAM-1 ligands on T cells have also contributed in understanding that the activation of ATM/ATR kinases and the DNA damage response (DDR) is a common pathway regulating the expression of activating ligands in different types of cells and under different conditions. The functional consequences of NKG2D and DNAM-1 ligand expression on activated T cells are discussed in the context of physiologic and pathologic processes such as infections, autoimmunity and Graft Versus Host Disease (GVHD).